BERBAGAI PANDANGAN TENTANG PRODUKTIVITAS - -, Suwarto (Universitas Slamet Riyadi, 2009)
ABSTRACT Productivity is better if it purpose as a measurement for determining how much of resources be used in organization to reach enterprises purpose. Requisite for improving productivity if management can be able to measure out-put and input. Because of that, management have to get ratio which that bigger between output and input. The ratio is called Index Productivity. Index Productivity shows a mount of acceptance product be divided by total product in the same time. Keywords: national, plane, industry, labor individual, enterprise, output, index,productivity.